2020
DOI: 10.1371/journal.pone.0238116
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of wheelchair users with spinal cord injury on fall circumstances and fall prevention: A mixed methods approach using photovoice

Abstract: Introduction Wheelchair users with spinal cord injury are at a high risk of falls. However, the perspectives of wheelchair users with spinal cord injury on their fall circumstances and their preferences for fall prevention strategies/interventions remain understudied. Therefore, we aimed to: a) describe the circumstances of falls experienced by wheelchair users with spinal cord injury over a six-month period, b) explore their perspectives of why falls occurred in certain situations, and c) explore their perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…These findings are consistent with previous studies examining the circumstances of falls among ambulators and wheelchair users with SCI/D. 5 , 12 , 28 , 41 Individuals with SCI/D have explained that home is a “safe space” where they are less vigilant about preventing falls. 41 Further, higher activity levels during the daytime may explain the high fall occurrence in the morning and afternoon.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous studies examining the circumstances of falls among ambulators and wheelchair users with SCI/D. 5 , 12 , 28 , 41 Individuals with SCI/D have explained that home is a “safe space” where they are less vigilant about preventing falls. 41 Further, higher activity levels during the daytime may explain the high fall occurrence in the morning and afternoon.…”
Section: Discussionsupporting
confidence: 91%
“… 5 , 12 , 28 , 41 Individuals with SCI/D have explained that home is a “safe space” where they are less vigilant about preventing falls. 41 Further, higher activity levels during the daytime may explain the high fall occurrence in the morning and afternoon. 41 Consistent with prior research, 5 , 28 walking was the most commonly performed activity at the time of a fall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 147 articles for full-text review, 131 were excluded because of their natures of case series (n = 9) or review article (n = 1), no information on outcomes (n = 35), content not related to the present study (n = 52), recruitment of only DVT patients (n = 29), mixed thromboembolic events (n = 4), and the use of extracorporeal membrane oxygenation (ECMO) in some patients (n = 1). Finally, a total of 16 studies with 5826 patients were included in the current meta-analysis 20 34 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants were as likely to fall during standing as during walking, which is different than in previously reported studies, where more falls in people with iSCI/D occur while walking ( 57 59 ). However, the participants in these studies were all full-time ambulators, while some participants in our study used a wheelchair as their primary means of mobility, and previous research has shown that walking is not commonly associated with falls for this group ( 60 ). It is likely that our findings reflect the common activities associated with falls for both ambulators and wheelchair users.…”
Section: Discussionmentioning
confidence: 88%